Russia: The Long Road to Ratification. Internal Institution and Pressure Groups in the Kyoto Protocol's Adoption Process - Barbara Buchner; Silvia Dall'Olio (Fondazione Eni Enrico Mattei (FEEM), 2004)
The Russian Federation played a crucial role in the ratification of the Kyoto Protocol. Indeed, after the US decision not to comply with the treaty, its ratification turned out to be indispensable for the Protocol to become legally binding. In early 2002, the Russian government decided to initiate the ratification process. However, notwithstanding this initial commitment, the country long hesitated to fulfil its promises, and for the last two years it sent numerous contradictory signals with respect to its position on climate policy. As a consequence, the factors that shape Russia's behaviour in the context of climate negotiations received increasing attention. The main focus has been on the economic and international aspects motivating the Russian strategy. This paper attempts to complete this analysis by concentrating on a further feature that significantly contributed to Russia's final decision, namely domestic forces. These factors have often been overlooked in the discussion of the Russian strategy. In order to fill this gap, this paper reconstructs the Russian ratification process, trying to identify the main domestic players and their role. Our findings provide various indications on the reasons of the recent developments in Russia, confirming the key role of the Russian President.
Keywords: H11; P27; P28; Q28; Q58; 330; Agreements; Climate; Incentives; Negotiations; Policy; Klimaschutz; Umweltabkommen; Verhandlungen; Russland; Politische Entscheidung